Application of supercritical CO2 for wafer processing steps - Tse, Man Siu. (2008)
Invention disclosures have been submitted to NTU for consideration. 1. Method of Forming Palladium Seeding nanoparticles and Film on Barrier Layer for Copper Metallization in Semiconductor Wafer Manufacturing Abstract A method for the deposition of noble metal nanoparticles or thin film such as the noble metal Palladium nanoparticles or thin film for example, over the barrier layer surface for the purposes of copper metallization in wafer manufacturing by supercritical chemical fluid deposition. The method involves the noble metal organic precursors, such as the palladium metal organic precursors that can be reduced by alcohol or its derivatives to metal atoms in the supercritical chemical fluid processing at low temperature. Noble metal nanoparticles or thin film such as the palladium nanoparticles or palladium thin film, for example, can be deposited on the surface of the barrier layer for deep submicron copper metallization in the supercritical chemical fluid in semiconductor wafer manufacturing. 2. Method of forming metal nanoparticles and metal film on pore surfaces of porous substrates for hydrogen storage, separation and purification Abstract A process for the deposition of metal nanoparticles and metal thin film such as the noble metal Palladium nanoparticles, for example, for the purposes such as hydrogen storage, separation and purification, for example, over the nanopores or pore surfaces of porous substrates by supercritical chemical fluid deposition. The process involves the metal organic precursors, such as the noble metal palladium metal organic precursors, that can react with alcohol and its derivatives to metal atoms in the supercritical chemical fluid processing at low temperature. Metal nanoparticles or thin film such as the noble metal palladium nanoparticles and continuous palladium thin film, for example, can be deposited on the surfaces of the nanopores or pores of the porous substrates in the supercritical chemical fluid. The porous substrates can be of rigid materials such as alumina, glass, stainless steel, for example, and semi-rigid materials such as polymer membranes, for example, typically used for fluid filtration. The properties and characteristics of the metal nanoparticles and metal films such as the palladium nanoparticles, for example, are determined by the pressure of supercritical fluid, the temperature of supercritical fluid, the type of the porous structures, the molar ratio of metal metal organic precursors to alcohol or its derivatives and the reaction time.